Unraveling the Complexity: A Comprehensive Analysis of the Armenia-Azerbaijan Conflict and Turkish Geopolitical Stance - Nizhum, Tasnim Zerin (Society & Sustainability, 2025)
The Armenian Azerbaijani dispute, a 100-year-old conflict, has resurfaced in the Nagorno-Karabakh region, a region with a majority Armenian population. The Armenia-Azerbaijan conflict began after Russia’s 1917 Bolshevik Revolution, with Azerbaijanis and Armenians fighting for sovereignty over Nagorno-Karabakh. After the USSR’s dissolution in 1991, the conflict resulted in 20,000 deaths and over 1 million displaced persons. This paper examines the historical background of the Armenia-Azerbaijan conflict over Nagorno-Karabakh, a region with a majority Armenian population. It also analyzes the reasons behind the escalation of the conflict in 2020 and Turkey’s role in supporting Azerbaijan. The study employs a descriptive secondary data analysis approach, reviewing various reports, journals, articles, and research papers. The findings reveal that the conflict stems from historical ethnic tensions and territorial disputes. Azerbaijan’s military advantage due to increased energy resources, Turkey’s political and military support, and the withdrawal of the United States from the region all contributed to the recent escalation. The war resulted in casualties on both sides and caused economic damage. Turkey aims to expand its influence in the area by supporting Azerbaijan. The paper concludes that the conflict will unlikely be resolved soon due to the complex geopolitical interests involved.